2019
DOI: 10.5897/ajbm2019.8876
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management constraints in Tanzanian small and medium enterprises

Abstract: Supply chain management (SCM) has gained popularity around the globe due to its significance in relation to improving business performance. Although large enterprises have been able to successfully implement SCM, it is different in small and medium enterprises (SMEs) as they are faced with several constraints that hinder the effective implementation of SCM. Variables such as technological difficulties, poor coordination with the supplier's lack of government support, resources, funds, access to markets and top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…processing sector in Tanzania. The 13 informants were found to be suitable as has been suggested by previous researchers Nkwabi (2019) and Dai et al (2019). They also suggest that a minimum of 12 informants is sufficient for a researcher to reach saturation.…”
Section: The Tanzanian Food Sectorsupporting
confidence: 59%
See 2 more Smart Citations
“…processing sector in Tanzania. The 13 informants were found to be suitable as has been suggested by previous researchers Nkwabi (2019) and Dai et al (2019). They also suggest that a minimum of 12 informants is sufficient for a researcher to reach saturation.…”
Section: The Tanzanian Food Sectorsupporting
confidence: 59%
“…In Tanzania Katunzi and Zheng (2010) found that Tanzanian SMEs fail to effectively implement SRM due to the lack of trust among the partners. Nkwabi (2019) reported that poor coordination was a major factor impacting SRM in the Tanzanian SMEs. Although previous researchers have identified SRM issues in the SMEs, there is a dearth of literature in the Tanzanian context, particularly in the food processing sector.…”
Section: Srm In Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…When effectively enforced, CRM and SRM lead to a positive impact on firms' performance. Practices such as early buyer and supplier involvement in product development LBSJMR 21,2 help firms minimize product costs and shorten the time required for product design and development (Mkwabi, 2019;Uribe et al, 2019). Furthermore, improved relationships along the supply chain result in the timely delivery of better-quality materials at a cost-effective, which are the primary drivers of firms' profitability and financial sustainability.…”
Section: Suppliers and Customers Relationships Managementmentioning
confidence: 99%
“…Empirical evidence has identified a lack of awareness regarding the perceived benefits of SSCMPs, financial constraints in supporting SSCMPs, a lack of trust and poor coordination and support from top management as key barriers to the effective adoption of SSCMPs, especially in low- and middle-income countries (Mangla et al , 2018; Mkwabi, 2019). Türk and Çelik (2019) suggest that proper planning, top management support and commitment, a sound financial position and an innovative culture are necessary to overcome these barriers and promote the adoption of SSCMPs by SMEs.…”
Section: Introductionmentioning
confidence: 99%